Discharge coefficient of broad crested weir with various degree of side contractions - Visan Vongtanasunthorn; Nir, Zeev; Kinori, Ben-Zion; Ackermann, Norbert L.; Italian Government and the Asian Institute of Technology, IeScholarship Donor (Bangkok : Asian Institute of Technology, 1975)
A study of the discharge coefficient of broad crested weir with various degree of side contractions is presented, The discharge equation is obtained by dimensional analysis, and the discharge coefficient is related to dimensionless ratios that describe the geometry of the channel, weir and the characteristic of the flow. The effect of these various ratios on the discharge coefficient is shown by the use of the laboratory data. The experiments were carried out by using two different radius of entrances of the broad crested weir, four various radius of entrances of the side contractions and with nine degrees of side contractions. Also the profiles of water surface and locations of critical for the flows on the broad crested weir are presented.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand .
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Weirs; Hydraulic structures; Dams